The work-family interface and child mental health: longitudinal associations via family functioning across childhood - Vahedi, Andisheh (My University, 2019)
Work-family conflict and enrichment refer respectively to the difficulties and benefits that parents experience when combining work and family responsibilities. Very little research exists on the crossover of parents’ work-family experiences to family functioning and child mental health. The present thesis incorporated three studies, and used data from the Longitudinal Study of Australian Children dataset, and aimed to investigate longitudinal associations between parents’ work-family experiences (conflict and enrichment) and child internalising, externalising, and disordered eating problems via the family functioning factors of inter-parental conflict (i.e., verbal arguments between parents) and parenting irritability (i.e., angry and inconsistent parenting). Study 1 used structural equation modelling (N = 2158 children, 2181 adolescents) to investigate the mediating role of inter-parental conflict in the association between mothers’ work-family conflict and enrichment, and child internalising and externalising problems, and partial syndromes of anorexia and bulimia nervosa over two distinct developmental pathways of childhood and adolescence. Results provided evidence of a mediating role of inter-parental conflict at 6-7 years in the association between mothers’ work-family conflict at 4-5 years and child internalising problems at 8-9 years. There was no evidence for the association between work-family enrichment and child mental health, or between work-family experiences and disordered eating variables. Study 2 used growth curve modelling to assess the rate and shape of change, and direction of associations between mothers’ work-family conflict, enrichment, inter-parental conflict, and child internalising and externalising problems (N = 2946). Results supported bidirectional associations between work-family experiences and child mental health. Initial levels of mothers’ work-family conflict at 4-5 years predicted more rapid increases in child internalising problems from 4-5 to 14-15 years, and initial child internalising problems at 4-5 years predicted more rapid reductions in mothers’ work-family enrichment from 4-5 to 14-15 years. Initial work-family enrichment at 4-5 years predicted more rapid reductions in inter-parental conflict from 4-5 to 14-15 years, but inter-parental conflict was not found to be associated with the rate of change in work-family conflict or enrichment over time. Further, initial inter-parental conflict at 4-5 years was found to be associated with more rapid increases in child externalising problems from 4-5 to 14-15 years, but not vice versa. Study 3 used path analysis (N = 3061) to investigate the crossover influences from mothers’ and fathers’ work-family conflict to each parent’s perception of inter-parental conflict and parenting irritability, and subsequent influences on children’s internalising and externalising problems. Results showed crossover from each parent’s work-family conflict to their own and to the other parent’s functioning on measures of inter-parental conflict and parenting irritability. Mothers’ and fathers’ parenting irritability at 6-7 years fully mediated the association between mothers’ work-family conflict at 4-5 years and mother-reported child externalising problems at 8-9 years. Mothers’ parenting irritability at 12-13 years fully mediated the association between fathers’ work-family conflict at 10-11 years and both mother- and adolescent-reported externalising problems at 14-15 years. Overall, results across the three studies illustrate the important role that both parents’ work-family experiences play in their children’s development, with implications for targeting intervention strategies to promote positive functioning of working parents in the home environment, in order to best support children’s mental well-being.
Keywords: Families; Families -- Work/family Balance; Families and relationships; Families; Work/family Balance; Families and relationships